THE EMERGENCE OF THE EXISTENT MOVEMENT IN TURKEY AND ITS MAIN IDEAS - Ashurova Dilrabo Isroilovna (Zeta Repository, 2023)
In this article, the national, cultural and educational revival, which began among the peoples of Central Asia, the Caucasus, and Central Siberia, which were considered Russian colonies in the late XIX and early XX centuries, was manifested as a modernist movement. Turkestan Jadids promote the idea of liberating the people from backwardness and religious superstition, reforming the principles of Sharia, spreading enlightenment to the people, and achieving national autonomy. The Jadids sought ways to renew and improve society with national unity, spiritual and educational reforms. about the word _ goes